Histological Changes in Mice (Balb/c) Induced by Newcastle Virus in Digestive System - Abbas Abed Sharhan1, Ahmed Obaid Hussain2, Ameer Jawad Hadi3, Ruqya jaafer baqer3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Many domestic and Newcastle disease is a contagious bird disease affecting wild avian species,it may be transmissible to humans . Detection of Newcasstle virus confirmed by rapid test technique(Immunochromatography) . ten sample (10% ) out of 100 fasces sample collected from chickens were positive. Twelve mice used in this study devided into two groups ,first group consist of six mice induced with 0.2 ml from one positive sample of Newcasttle virus suspension to evaluate some histopathological changes caused by Newcasstle virus in small intestine and stomach of mice,second group induced with 0.2 ml from phosphate buffer saline only. The results revealed that histopathological changes in small intestine (duodenum )induced by using 0.2 ml from the positive Newcasstle virus suspension to complete necrosis and fragmentatin in the villi.Jejenum of mice treated with this concentration of Newcasstle virus has partial necrosis for villi with filtration of villus core while ilium of mice treated with same concentration has wide spread of villus necrosis . Stomach of treated mice has oedema in submucosa layer and partial necrosisin gastric glands.